Performansi Genotip Padi Beras Merah dari Varietas Lokal Aceh yang Dibudidayakan secara Aerobik pada Sistem SRI Organik - Efendi Efendi; Syamsuddin Syamsuddin; Betti Agustina (Jurnal Floratek, 2016)
Performance of Red Rice Genotype from Aceh’s Province that Cultivated with Aerobic System in Organic SRI ABSTRACT. Characterization of the performance on morpho-agronomic brown rice originating from local varieties of Aceh has been done in order to develop new varieties that adapt to climate change and suitable for organic SRI method. Eighteen red rice genotypes have been planted to evaluate the characters based on the method of cultivation in aerobic system. The red rice genotypes were observed and showed the variation in very significant to the formation of tillers, plant height, number of panicles, panicle length, grain weight per plant, 1000 grain weight, and grain yield potential. The results showed that the genotypes studied had high genetic diversity. Tillering in red rice varies between 19-30 days after sowing. The highest plant height found in genotype Pade Mirah 44, while the lowest plant found in genotype Sipulo Mirah. It was dicovered that the number of panicle significantly affected by the red rice genotype. Number of red rice panicle ranged between 14-48 per plant. The number of panicles in genotype Ketan Mirah was higher than genotype of Meuligai Mirah. However, Ketan Mirah 2 had the shortest panicles. Grain weight per panicle significantly also affected by red rice genotypes. The highest grain weight found in genotype Pineung Lango 172. In addition, also found that the weight of 1000 grain red rice was significantly different between the genotypes. The smallest size of a grain found in genotype of Sirias 102, whereas genotype Pade Mas 41 showed the largest size of grain (30.8 g). Research showed that genotypes affect grain yield potential significantly. The highest yield potential obtained from the genotype Pineung Lango 172 (6.8 ton/ha). In contrast, the lowest result was found in genotype Sipulo Mirah (2.8 tons/ha). Therefore, the results of the present invention is expected to provide information to enhance the sustainability of rice plant breeding system of organic red rice according to SRI system.